Gamma-ray emission from early-type stars interacting with AGN jets - Araudo, Anabella Teresa (2013)
We study the interaction of early-type stars with the jets of active galacticnuclei. A bow-shock will form as a consequence of the interaction of the jetwith the winds of stars and particles can be accelerated up to relativisticenergies in these shocks. We compute the non-thermal radiation produced byrelativistic electrons from radio to gamma-rays. This radiation may besignificant, and its detection might yield information on the properties of thestellar population in the galaxy nucleus, as well as on the relativistic jet.This emission is expected to be relevant for nearby non-blazar sources.